SMARANDACHE EĞRİLERİNİN DİFERENSİYEL GEOMETRİSİ - GÜLTEKİN, HURİYE (Fırat Üniveristesi, 2015)
Bu çalışma dört bölümden oluşmaktadır. Birinci bölümünde Öklid uzayının bazı temel tanımları verildi.İkinci bölümde; Minkowski uzayının temel tanım ve teoremleri verildi. Üçüncü bölümünde; 3-boyutlu Öklid uzayında özel smarandache eğrileri incelenmiştir. Dördüncü bölümünde; Minkowski uzayında smarandache eğrileri incelenmiştir.

This study is consisted of four chapters: In the first chapter, some basic definition and theorems of Euclidean 3-space are given. In chapter 2, some basic definition and theorems of Minkowski space are given. In chapter 3, special smarandache curves in the Euclidean 3-space are given. In chapter 4, smarandache curves in the Minkowski space are researched.
Differential geometry of Smarandache curves
Keywords: Matematik